What factors differentiate an effective employment equity implementation strategy from an ineffective strategy in South African organisations and how does this impact on employees' perceptions of organisational justice? - Woolley, Robin (University of Pretoria, 2016)
Mini-disseration (MBA)--University of Pretoria, 2015.